The Effects of Acute Smoking on Platelet Behaviour, Fibrinolysis and Haemorheology in Habitual Smokers - Belch, J J F; McArdle, B M; Burns, P; Lowe, G D O; Forbes, C D (Thrombosis and Haemostasis, 1984)
There is an increased frequency of arterial thrombosis in cigarette smokers. The changes in blood coagulation seen in these subjects have been studied by many workers but results have not always been in agreement. We wished to study the effects of acute .smoking on platelet behaviour, fibrinolysis and haemorheology in ten habitual smokers, and to compare these results with nonsmoking controls. Results show that the smoking group had higher plasma fibrinogen (p <0.04), lower plasminogen (p <0.02) and plasminogen activator (p <0.05), and higher plasma viscosity (p <0.003). The changes seen in cigarette smokers after smoking three cigarettes were an increase in the rate of platelet aggregation to ADP (p <0.02), an increase in α2M, (p <0.02), and factor VIII RAG (p <0.05). Plasma viscosity was decreased (p <0.02) as was red cell deformability (p >0.02).We confirm an increased tendency to hypercoagulability in smokers compared to controls which becomes more pronounced immediately after smoking three cigarettes.
Keywords: Cigarette smoking; Platelets - Fibrinolysis; Red cell deformability; Blood viscosity; Plasma viscosity